Comparación de los perfiles y parámetros de combustión y oxi-combustión para la cascarilla de arroz (2016)
ABSTRACT: Profiles and kinetic parameters of combustion and oxy-combustion processes of rice husk were compared using a thermogravimetric analyzer (TGA) and the obtained data was processed by a non- isothermal method. Increasing heating rates and O2 concentrations make combustion and oxy-combustion profiles narrower as a consequence it conduces to instantaneous mass lost and shorter consumption time. Additionally, activation energies for O2/CO2 mixtures are lower compared to those of O2/N2, indicating that the possible gasification reactions between CO2 and the surface of carbonized rice husk under oxycombustion conditions would not been taking place or are negligible.